The Theban plays - Sophocles (Agora editions (Cornell University Press), 2014)
The timeless Theban tragedies of Sophocles-Oedipus the Tyrant, Oedipus at Colonus, and Antigone-have fascinated and moved audiences and readers across the ages with their haunting plots and their unforgettable heroes and heroines. Now, following the best texts faithfully, and translating the key moral, religious, and political terminology of the plays accurately and consistently, Peter J. Ahrensdorf and Thomas L. Pangle allow contemporary readers to study the most literally exact reproductions of precisely what Sophocles wrote, rendered in readily comprehensible English. These translations enable readers to engage the Theban plays of Sophocles in their full, authentic complexity, and to study with precision the plays' profound and enduring human questions. In the preface, notes to the plays, and introductions, Ahrensdorf and Pangle supply critical historical, mythic, and linguistic background information, and highlight the moral, religious, political, philosophic, and psychological questions at the heart of each of the plays. Even readers unfamiliar with Greek drama will find what they need to experience, reflect on, and enjoy these towering works of classical literature.